Mixed binary integer programming formulations for the reentrant job shop scheduling problem - Pan, Jason Chao-Hsien; Chen, Jen-Shiang (Computers & operations research, 2005)
This paper describes the development of mixed binary integer programming (BIP) formulations for the reentrant job shop scheduling problem. Based on an earlier classical job shop model developed by Manne and improved by Liao and You, this paper presents two extended BIP optimization formulations for the problem under consideration. In order to improve the solution speed of the BIP formulations, two layer division procedures are developed and incorporated in the corresponding models. Results of computational experiments, in which an average performance of these formulations is investigated, are also reported.